2016
DOI: 10.1039/c6ra05411k
|View full text |Cite
|
Sign up to set email alerts
|

Green and catalyst-free preparation of triazinyl polyimide for the efficient adsorption of glycoproteins

Abstract: Triazinyl polyimide is prepared via a solvent-free and catalyst-free imidization reaction by using melamine and pyromellitic dianhydride as precursors and it exhibits excellent selectivity towards glycoprotein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Particularly, the diffraction peak at 18.8° (interlayer spacing ( d ) = 0.474 nm) and the peak at 29.5° ( d = 0.304 nm) indicated that the synthesized polymers were reasonably crystalline. , The percentage crystallinity and average crystallite sizes of the polymers were suitably computed (Table S1). , The XRD pattern of thiourea/PI manifested that the incorporation of thiourea-derived sulfur into PI had presumably improved on the uniformity of polymer chain orientation and molecular coherence of the crystal domains . A shift in the peak position from 26.6° ( d = 0.334 nm) to 27.6° ( d = 0.322 nm) also indicated that the aromatic segments of the modified PI were more regularly stacked .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the diffraction peak at 18.8° (interlayer spacing ( d ) = 0.474 nm) and the peak at 29.5° ( d = 0.304 nm) indicated that the synthesized polymers were reasonably crystalline. , The percentage crystallinity and average crystallite sizes of the polymers were suitably computed (Table S1). , The XRD pattern of thiourea/PI manifested that the incorporation of thiourea-derived sulfur into PI had presumably improved on the uniformity of polymer chain orientation and molecular coherence of the crystal domains . A shift in the peak position from 26.6° ( d = 0.334 nm) to 27.6° ( d = 0.322 nm) also indicated that the aromatic segments of the modified PI were more regularly stacked .…”
Section: Results and Discussionmentioning
confidence: 99%
“…22,23 The XRD pattern of thiourea/PI manifested that the incorporation of thiourea-derived sulfur into PI had presumably improved on the uniformity of polymer chain orientation and molecular coherence of the crystal domains. 24 A shift in the peak position from 26.6°(d = 0.334 nm) to 27.6°(d = 0.322 nm) also indicated that the aromatic segments of the modified PI were more regularly stacked. 25 The progressive diminution of the peak at 18.8°and the concomitant appearance of a weak peak at 13.2°(d = 0.673 nm), following the gradual increase in SWO 3 content, represented a slightly altered in-planar packing motif similar to the periodic tri-s-triazine connection ordinarily manifested by the structure of g-C 3 N 4 12 .…”
Section: ■ Materials and Methodsmentioning
confidence: 96%
“…Additionally, the poor solubility of imide units in traditional solvents also causes early desolvation and phase separation, making it hard to evolve the integrated porous structure in the resultant polymers. [11][12][13][14] Therefore, it is imperative to explore the sustainable preparation strategy of MPIs for promoting their practical applications.…”
Section: Introductionmentioning
confidence: 99%